Polemik Sultan Perempuan di Yogyakarta - Muhammad Rifa’at Adiakarti Farid (Rumah Jurnal Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2018)
Yogyakarta is led by a Sultan who concurrently serves as governor. The sultan who ruled at this time, Sultan Hamengkubuwa X did not have a son to be appointed as crown prince but according to court customs, if he did not have a son then the royal throne would fall to the sultan's younger brother. At present, the Sultan has appointed his eldest daughter to be the legitimate heir to the royal throne, contrary to customs. This raises the pros and cons of the internal and external courts. This paper looks at the issue of the appointment of the crown princess as the victory of the struggle of the women's movement to achieve equal rights and degrees towards men